2021
DOI: 10.1155/2021/4403456
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mechanism of Gob‐Side Roadway under Overlying Coal Pillar Multiseam Mining

Abstract: Roadway deformation and rock burst are the two key challenges faced by the safe operation of coal mines. Aiming at the issue of large deformation of the gob-side roadway under coal pillars in multiseam mining, this study has considered the case of the 8308 panel of Xinzhouyao coal mine in China. Based upon a combination of theoretical analysis, numerical simulations, and engineering practices, the mechanical model of “stress and deformation quantitative calculation of gob-side roadway under overlying coal pill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Numerous scholars have explored the failure mechanism characteristics and spatial extent of surrounding rock in mining roadways under various conditions 23 – 26 . Wu Xiangye et al 27 identified the mechanical mechanism behind the asymmetric expansion of the plastic zone by examining the failure mechanism of mining roadways on a gentle slope and at close proximity.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous scholars have explored the failure mechanism characteristics and spatial extent of surrounding rock in mining roadways under various conditions 23 – 26 . Wu Xiangye et al 27 identified the mechanical mechanism behind the asymmetric expansion of the plastic zone by examining the failure mechanism of mining roadways on a gentle slope and at close proximity.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing demands of coal resources and the construction of resource-saving coal mines, the implementation of narrow coal pillars to arrange working faces has become a more popular choice of more mines [1][2][3]. However, large deformation and damage of the GSR has also become a large problem, plaguing safe production in mines, especially for close extra-thick coal seams.…”
Section: Introductionmentioning
confidence: 99%